Unusual clinical presentation and neuropathology in two subjects with fused‐in sarcoma (FUS) positive inclusions - Hartikainen, Päivi H.; Pikkarainen, Maria; Hänninen, Tuomo; Soininen, Hilkka; Alafuzoff, Irina (Neuropathology, 2012)
We report two unusual autopsy cases with frontotemporal lobar degeneration (FTLD) that were hyperphosphorylated‐tau‐ and TAR DNA binding protein 43 (TDP‐43)‐ negative. The behavioral symptoms in both cases were compatible with frontotemporal dementia, but they exhibited more prominent speech and language related symptoms than previously reported. Moreover, they displayed a short duration of the disease; the male case had a disease onset age of 45 years, and duration of 5 years, and the female case suffered even shorter disease duration and a later onset of the symptoms, at the age of 67 years. Moreover, the motor functions had deteriorated in different ways in these cases. The male patient showed progressive motor symptoms, weakness of extremities and bulbar muscles suggesting motor neuron disease with a muscle biopsy supporting neurogenic deficits, whereas the female patient exhibited dyskinesias and tremor with progressive swallowing disorders. The father of the male case displayed dementia of similar type at the age of 68 years. In both cases, neuropathological examination showed fused‐in sarcoma (FUS)‐positive pathology. The male patient had intensely FUS‐positive cytoplasmic and intranuclear inclusions that resembled the characteristics previously reported in FTLD FUS, whereas the female patient did not exhibit any cytoplasmic inclusions but had roundish, dense FUS‐positive intranuclear inclusions. She also displayed a plethora of other pathologies including α‐synuclein, hyperphosphorylated‐tau, β‐amyloid aggregation and some neuronal polyglutamine aggregation (1C2) but no well‐demarcated inclusions were observed. We conclude that clinical phenotypes of FUS pathologies also include elderly patients and are more variable with motor and speech disorders than previously reported.